ANALYSIS REMANING LIFE ASSESSMENT (RLA) SHELL 1st STAGE SEPARATOR USING API 510 STANDARD - Muhammad Syaukani; Suharno Suharno; Irza Sukmana; Iqbal Mahesa; Eko Pujiyulianto (Jurnal Vokasi Mekanika (VoMek), 2024)
This study aims to conduct a Remaining Life Assessment (RLA) on the shell 1st stage separator. The process is carried out through the stages of calculating the minimum permissible shell thickness, MAWP, corrosion rate, and determining the operational feasibility of the separator. The method used is non-destructive test (NDT) inspection to determine the minimum actual thickness. Calculations were made using the API 510 standard. Based on the evaluation of the minimum thickness and MAWP value, the 1st separator shell is still feasible to operate. The ST corrosion rate that occurred in 2012, 2016, and 2019 was 0.123 mm/year, respectively; 0.007 mm/year; and 0.023 mm/year. While the LT corrosion rate is 0.089 mm/year, RLA analysis shows that the remaining life in 2012 was 93.75 years, 93.42 years in 2016, and 92.63 years in 2019. Thus, the shell 1st stage separator is still feasible to operate.